MORFOLOGI DAN TIPE STOMATA DELAPAN SPESIES BAMBU KOLEKSI KEBUN RAYA EKA KARYA BALI - Faizun Nadhiyah Nitawaro; Made Pharmawati; Ni Made Gari; Arief Priyadi (SIMBIOSIS, 2024)
Eka Karya Bali Botanic Garden is one of the ex-situ plant conservation centers in the island of Bali. There are various collections of plants, one of which is bamboo. Indonesia is estimated to have 176 species of bamboo which is more than 12% of the world's bamboo species. The Eka Karya Bali Botanical Garden has a collection of 58 bamboo collections. Several genera among the existing bamboo collections, namely Bambusa, Gigantochloa, Schizotachyum and Neololeba need to be characterized morphologically. This study aimed to analyze the morphological and types of stomata on eight bamboo species (Neololeba atra, Bambusa maculata, Bambusa ooh, Giganthochloa apus, Giganthochloa aya, Giganthochloa taluh, Schizostachyum lima, dan Schizostachyum silicatum) from the “Eka Karya” Botanical Garden collection. The morphological characters observed were bamboo clumps, stems color, branches, reed sheaths color, and leaves. For observation of stomatal characteristics, the type and density of stomata were observed by making a replica of the lower epidermis of the leaf and observing it under a microscope with a magnification of 400x. The results showed that the morphological characters of the eight bamboo species had dense clumps and lateral branches but there were differences in the color of the stems, sheath, upper and lower surfaces of the leaves, while the type of stomata was the same, namely the type Gramineae. Keywords: Bamboo, stem, leaf, morphology, stomata